Reliability of sports related functional tests with emphasis on speed and agility in young athletes - Alricsson, M.; Harms-Ringdahl, K.; Werner, S. (Scandinavian Journal of Medicine & Science in Sports, 2001)
The aim of the present investigation was to test the reliability of two sports related functional tests, a speed test (slalom-test) and an agility test (hurdle-test). Eleven athletes aged 11 years (8 boys, 3 girls) participated voluntarily in the study. All subjects completed four different test sessions for both the slalom-test and the hurdle-test using six standard track hurdles placed at 2-m intervals along a 12-m length of track. There were no significant differences between testing sessions for either the slalom-test (P=0.99) or the hurdle-test (P=0.96), showing no systematic variation between test times. The intraclass correlation coefficients were 0.96 and 0.90 respectively, indicating a good reliability. We conclude that the slalom-test and the hurdle-test are reliable sports related functional tests for measuring speed and agility in groups of young athletic individuals.